PERLINDUNGAN SOSIAL ANAK TELANTAR OLEH PANTI ASUHAN TAMAN HARAPAN MUHAMMADIYAH KOTA BANDUNG - Zahra Arianto, Hasna; Aritonang, Admiral Nelson; Mildawati, Milly (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Social protection encompasses all efforts directed towards preventing and addressing risks arising from social vulnerabilities. Social protection consists of five main elements: social assistance, social insurance, labor markets, community-based micro schemes, and child protection. This research aims to provide an overview of: 1) assistance for orphans, widows, the destitute, and abandoned children; 2) guarantees for education, health, and employment; 3) training and apprenticeships for foster children; 4) fundraising for communities outside of orphanages; and 5) the fulfillment of child development carried out by Taman Harapan Muhammadiyah Orphanage in Bandung City. This research utilizes a qualitative approach with a descriptive design. The data collection techniques used are: 1) participatory observation; 2) interviews; and 3) document studies. To ensure data validity, the researcher employed credibility tests, including: 1) source triangulation; 2) the use of reference materials; and 3) member checks. The results of the study indicate that the social protection provided by Taman Harapan Muhammadiyah Orphanage in Bandung City is quite good, as it offers assistance in education, health, and other basic needs for abandoned, orphaned, and destitute children. Social protection is implemented through various programs, including the provision of grants, guarantees, child development support, and skills training.